Xanthoma of the Occipital Bone and With Preserved Inner and Outer Bone Cortex: Case Report - Broadway, S. Jared; Arnautovic, Kenan I.; Zhang, Yanlong (Journal of Neurological Surgery Reports, 2013)
Objective We present a unique case of a midline xanthoma of the occipital bone exhibiting atypical imaging characteristics with preserved bone cortex that has not previously been described.Participant This man presented with refractory headaches and suboccipital pain and a mass within the diploe of the occipital bone but with preserved inner and outer cortex of the bone. Magnetic resonance imaging showed a midline, enhancing, and marrow-replacing process in the occipital bone measuring 1.5 cm in anteroposterior (AP) diameter, resulting in mild indentation of the dorsal aspect of the cerebellar vermis.Results The patient underwent a suboccipital craniectomy. Tumor resection was from the foramen magnum to the inion and laterally until normal bone was encountered. The xanthoma was yellowish and bled a moderate amount upon resection.Conclusion An isolated cranial xanthoma with preserved inner and outer bone cortex involving the occipital bone and of midline location has yet to be described. The differential diagnosis of osteoexpansile skull lesion with preserved bone cortex should now include xanthoma. Given the broad spectrum of imaging characteristics exhibited by this unusual diagnosis, surgical intervention is indicated from a diagnostic as well as a therapeutic standpoint.
Keywords: xanthoma; tumor; occipital bone; histology; skull base; neoplastic lesion